Is Cognitive Impairment a Risk Factor for Post-Stroke Depression? A Meta-Analysis Study - Dinda Ika Pratiwi; Didik Tamtomo; Bhisma Murti (Masters Program in Public Health, 2019)
Background: Depression is a psychiatric complication of stroke that often occurs and had a negative impact. Every year, 15 million people who experience strokes globally are at risk of developing post-stroke depression. Cognitive disorders are often associated with the presence of post-stroke depression. Understanding of risk factors for post-stroke depression can help in clinical identification and provide early intervention to improve stroke rehabilitation better. Therefore, it is very important to identify patients at risk for depression. This study aims to analyze cognitive impairment factors in the incidence of post-stroke depression.Subjects and Method: The meta-analysis was conducted from Pubmed, Science Direct, and Springer Link databases using